The Most Influential Factors On Stock Prices In The JII Index - Syaeful Bakhri; Faridah Nurbaiti; Ayus Ahmad Yusuf (Jurnal Manajemen, 2023)
This study determined the impact of changes in the Jakarta Islamic Index's Consumer Goods sector's Earnings Per Share, Return on Equity, and Gross Domestic Product from 2018 to 2020. This work uses panel data regression analysis and quantitative research techniques with secondary data. A purposive sampling method, or sample selection strategy based on several variables, was employed to choose the sample of firms in the consumer goods sector represented in the JII index. The F test results indicate that from 2018 to 2020, GDP, EPS, and ROE can impact the share price of JII issuers. According to the T-test, only EPS may have an enormous positive impact on stock prices, whereas ROE has a significant negative effect. GDP demonstrates that from 2018 to 2020, firms' stock prices in the consumer goods sector listed on JII are unaffected by GDP.